2019
DOI: 10.4103/jomfp.jomfp_200_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antifungal efficacy of different concentrations of Curcuma longa on Candida albicans: An in vitro study

Abstract: Background: Candidal infections have increased significantly in denture wearers, especially in immunocompromised patients. The increase in resistance to existing antifungal drugs and number of patients at risk, in conjunction with the restricted number of commercially available antifungal drugs that still present many side effects, are the cause for this problem. These limitations emphasize the need to develop new and more effective antifungal agents with lesser side effects. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…The extract showed antifungal activity against C. albicans in the agar well diffusion assay (10.2-27.1 mm inhibition diameter) and against T. rubrum (27.3-44.3 mm inhibition diameter). These results are in accordance with (Murugesh et al (2019) wherethey studied potent antifungal action of C. longa (alcoholic extract) against C. albicans. A. galanga has antifungal activity against filamentous fungi (Handajani and Purwoko 2008), Z. officinale (ginger) had pronounced antifungal activity, including strains that were highly resistant to amphotericin B and ketoconazole (Ficker et al 2003).…”
Section: Phytochemicalsupporting
confidence: 91%
“…The extract showed antifungal activity against C. albicans in the agar well diffusion assay (10.2-27.1 mm inhibition diameter) and against T. rubrum (27.3-44.3 mm inhibition diameter). These results are in accordance with (Murugesh et al (2019) wherethey studied potent antifungal action of C. longa (alcoholic extract) against C. albicans. A. galanga has antifungal activity against filamentous fungi (Handajani and Purwoko 2008), Z. officinale (ginger) had pronounced antifungal activity, including strains that were highly resistant to amphotericin B and ketoconazole (Ficker et al 2003).…”
Section: Phytochemicalsupporting
confidence: 91%
“…So far, phytochemicals have remained the leading source for potential antimicrobial agents, whether investigated independently or in a combination with another substance [2,25]. Recent studies have demonstrated a wide range of antimicrobial properties of curcumin mediated by different mechanisms, such as alteration of gene expression, inhibition of bacterial DNA replication and disruption of the bacterial cell membrane [26][27][28].Literature data demonstrate the beneficial and preventive role of curcumin against various microorganisms [29][30][31]. Despite various studies evaluating the antimicrobial activity of curcumin, further research is required with different concentrations against different strains of microorganisms.…”
Section: In Vitro Antimicrobial Activitymentioning
confidence: 99%
“…From this study, phytochemicals in turmeric have better antifungal activity working in combination than individual compounds [78]. Murugesh and colleagues elucidated that turmeric extracts exhibit a potent anticandidal effect against Candida albicans on in vitro studies [79]. In a randomized clinical trial, researchers demonstrated that the topical administration of curcumin 5% ointment can significantly reduce knee pain in osteoarthritis patients [80].…”
Section: Antifungalmentioning
confidence: 98%